Speech therapy, decision conflicts and dysphagic patients: an integrative review - Moreira, Márcio José da Silva (2021)
Dysphagia presents multidimensional negative impacts on the life of dysphagic patients and may generate decision conflicts related to their diet. This is a review of the literature on speech-language therapy, decision conflicts and the agents involved in the decision making process for deliberations related to the nutrition of this type of patient. This is an exploratory and descriptive study, with content analysis as proposed by Bardin. The databases used were PubMed, Scopus, Web of Science, Cochrane, Embase and Virtual Health Library. Conflicts involving the speech-language therapist, the patient, the family and the multidisciplinary team were identified. In the selected articles, no theory or methodwas identified to support the mediation of these conflicts. No Brazilian publications that answered the guiding question were found.